Unaccompanied Minors in Germany. A success story with setbacks? - Maren Zeller; Philipp Sandermann (Social Work and Society, 2018)
In Germany the issue of unaccompanied minors (UAM) has attracted increasing attention during recent years: politics, the media, professionals and researchers have all tried to react to the phenomenon adequately and"find solutions" to assumed problems. However, this paper reviews different aspects in regard to unaccompanied minors in Germany from a socio-pedagogical perspective. Firstly, insights into statistical data are given that reveal how heterogeneous the group of young people arriving and living in Germany is, despite the fact that they are all labelled the same (as UAM). Secondly, the changing legal and political framework for UAM reception in Germany is outlined and discussed. Thirdly, there is a focus on clearance practices and care arrangements for which the child and youth care system takes the main responsibility. Since the body of German research on this topic is far from being satisfactory, the conclusion points out the main gaps and challenges for future research.